An accurate transient model for temperature fluctuation on localized shear band in serrated chip formation. (15th August 2021) - Chen, Xuelin; Tang, Jinyuan; Ding, Han; Liu, Anmin
Highlights: 1 Experimentally validated modeling of temperature fluctuation at various serrated chip stages. 2 A novel method of accurately measuring temperature in chip segmentation process in micro-scale is presented. 3 The thermal fluctuation is strongly affected by cutting velocity, rake angle and chip formation time. 4 The area of maximum temperature in shear band is varying with chip formation process and cutting speed. The area can away from tool tip/rake face. 5 A discussion including temperature fluctuation, cutting forces, crack formation and deformation in chip segmentation process is addressed. Abstract: The temperature fluctuation process on localized shear band is an important foundation of the chip formation mechanism in mesoscopic scale of time (700-70 ms ) and dimension (65-500 um ). An accurate transient temperature fluctuation modeling of localized shear band is proposed by using the classic method of moving heat source and thermal convection in mesoscopic scale. Where, chip geometry, time coefficient of the coupling effect from relative chip segment, temperature rise from different heat sources and thermal convection model for chip segmentation process are developed, respectively. A novel measuring method are applied for thermal distribution in shear band and its evolution in chip generation progression. The given experimental and numerical results can show that the proposed temperature model can get the efficient predictions of temperature and physical phenomena at various chip segmentation stage. Physical phenomena in chip formation process, such as instable chip flow, crack generated and propagation, from the viewpoint of temperature fluctuation and its instable evolution, and cutting force are addressed and analyzed. The innovative model can determine the temperature fluctuation and evolution, area of maximum temperature of shear band in chip segmentation process in mesoscale of time and dimension. Graphical Abstract: Image, graphical abstract